A neonate with perianal cellulitis due to leukocyte adhesion deficiency - A case report - Jagannathan, Muthu Kumaran; Lingaldinna, Swapna; Vivek, S; Balasubramaniam, P (Indian Journal of Child Health, 2017)
Leukocyte adhesion deficiency (LAD) is a rare autosomal recessive disorder characterized by absence or dysfunctional CD18 on the surface of leukocytes due to a mutation in ITGB2 gene. The hallmarks of LAD are defects in leukocyte adhesion and marked leukocytosis. It is characterized by recurrent bacterial infections of the skin and mucosal membrane. Here, we report clinical and flow cytometric immunophenotyping of a baby diagnosed with LAD Type 1.